Amplitude and stride-to-stride variability of muscle activity during Lokomat guided walking and treadmill walking in children with cerebral palsy. (November 2020) - van Kammen, Klaske; Reinders-Messelink, Heleen A.; Elsinghorst, Anne L.; Wesselink, Carlijn F.; Meeuwisse-de Vries, Berna; van der Woude, Lucas H.V.; Boonstra, Anne M.; den Otter, Rob
Abstract: Background: The Lokomat is a commercially available exoskeleton for gait training in persons with cerebral palsy (CP). Because active contributions and variability over movement repetitions are determinants of training effectiveness, we studied muscle activity in children with CP, and determined (i) differences between treadmill and Lokomat walking, and (ii) the effects of Lokomat training parameters, on the amplitude and the stride-to-stride variability. Methods: Ten children with CP (age 13.2 ± 2.9, GMFCS level II(n = 6)/III(n = 4)) walked on a treadmill (±1 km/h; 0% bodyweight support(BWS)), and in the Lokomat (50% and 100% guidance; ±1 km/h and ±2 km/h; 0% and 50% BWS). Activity was recorded from Gluteus Medius (GM), Vastus Lateralis (VL), Biceps Femoris (BF), Medial Gastrocnemius (MG) and Tibialis Anterior (TA) of the most affected side. The averaged amplitude per gait phase, and the second order coefficient of variation was used to determine the active contribution and stride-to-stride variability, respectively. Results: Generally, the amplitude of activity was lower in the Lokomat than on the treadmill. During Lokomat walking, providing guidance and BWS resulted in slightly lower amplitudes whereas increased speed was associated with higher amplitudes. No significant differences in stride-to-stride variability were observed between Lokomat and treadmill walking, and in the Lokomat only speed (MG) and guidance (BF) affected variability. Conclusions: Lokomat walking reduces muscle activity in children with CP, whereas altering guidance or BWS generally does not affect amplitude. This urges additional measures to encourage active patient contributions, e.g. by increasing speed or through instruction. Highlights: Muscle activity in children with CP is reduced in the Lokomat. In the Lokomat, guidance and BWS result in slightly lower muscular amplitudes. Increasing speed results in higher amplitudes during Lokomat walking. Stride-to-stride muscle variability was similar during treadmill and Lokomat walking. Within the Lokomat only speed and guidance slightly affected muscular variability.